Mutagenicity tests on epristeride in vitro and in vivo - Wang Xiao-Lin; Zhen Wei-Jun; Wu Hong-Yan; Feng Jie; Tu Zeng-Hong (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the genetic effects of epristeride (Epr), a new prospective drug for treating benign prostatic hyperplasia. METHODS: 1) Assaying reverse mutation in histidine nutritional deficiency strain of Salmonella typhimurium 2) detecting chromosome aberrations in Chinese hamster lung cells (CHL); 3) micronucleus assays of mouse bone marrow; 4) counting sperm shape abnormalities 35 d after first ig Epr. RESULTS: 1) The reverse mutation happened at almost the same rate of the negative control. Epr did not induce bacterial mutation. 2) In vitro, the rates of aberration were all below 3%, thus Epr did not induce chromosome damage in CHL. 3) Micronucleated polychromatic erythroblasts (PCE) were not apparently more than those of sovent control, Epr did not induce the formation of micronuclei in PCE. 4) With Epr 818, 682, and 341 mg.kg-1, the head abnormalities of sperms were 5.3% +/- 2.7%, 5.3% +/- 1.9%, and 5.2% +/- 1.2%, respectively. CONCLUSION: No genetic toxicity of Epr was detected.